Análise de eficiência de tratamento de manipueira em reator anaeróbio de fluxo vertical com separação de fases - Machado, Eliane Pereira (2013)
The pollution potential of cassava is due primarily to high organic load, and the soluble sugars account for most of the organic matter of cassava. Because they are easily fermentable soluble and they degrade organic acids very quickly, enabling biological treatment, in particular anaerobic biological treatment. Thus, considering the expansion of cassava processing industry in the Paraná, this study aimed to verify the efficiency treatment of cassava in anaerobic reactor of a two-phase in an industry located in the central-western of state of Paraná. Throughout the period of operation of the bioreactor, it was found that the use of an alkalizing not to neutralize the acidity of the initial effluent committed the efficiency of the treatment system as a whole, mainly because of the small time to the research. The results of the characterization of the treated effluent showed that even with imbalance reaction and acidification, the reactor studied reduce by more than 90% of the turbidity values, over 60% volatile solids values and 40% reduced the values of COD and total nitrogen, so the anaerobic vertical flow with phase separation, showed great potential for the treatment of cassava, only if taken care of using dosages of alkaline to neutralize the natural acidity of cassava,especially early in the hydraulic retention time or during start-up of the reactor, in order to prevent the acidification complete of the effluent.